2021
DOI: 10.3390/ijms22158333
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Urolithin A on Mitochondrial Parameters in a Cellular Model of Early Alzheimer Disease

Abstract: (1) Background: Ellagitannins are natural products occurring in pomegranate and walnuts. They are hydrolyzed in the gut to release ellagic acid, which is further metabolized by the microflora into urolithins, such as urolithin A (UA). Accumulation of damaged mitochondria is a hallmark of aging and age-related neurodegenerative diseases. In this study, we investigated the neuroprotective activity of the metabolite UA against mitochondrial dysfunction in a cellular model of early Alzheimer disease (AD). (2) Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 70 publications
(114 reference statements)
3
31
1
Order By: Relevance
“…These and other observations [ 128 , 129 ] strongly suggest mitophagy enhancers are promising drugs to treat patients with AD and other tauopathies. However, these drugs need to be tested carefully using mouse models, particularly recently developed humanized Abeta knock-in (hAbKI) mice that express human amyloid beta peptide and exhibit late-onset AD features [ 130 , 131 ].…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…These and other observations [ 128 , 129 ] strongly suggest mitophagy enhancers are promising drugs to treat patients with AD and other tauopathies. However, these drugs need to be tested carefully using mouse models, particularly recently developed humanized Abeta knock-in (hAbKI) mice that express human amyloid beta peptide and exhibit late-onset AD features [ 130 , 131 ].…”
Section: Discussionsupporting
confidence: 54%
“…Defective mitochondrial biogenesis and accumulation of dead mitochondria are the main phenomena observed in age-associated diseases such as AD. Newly developed pharmacological treatments and novel chemical modulators like urolithin A [ 77 ], tomatidine [ 78 , 79 ], and actinonin [ 80 ] might be used to promote the efficient removal of dead and/or damaged mitochondria and restore energy homeostasis. Pharmacologic agents and natural supplements that target mitophagy are potential drugs which may enhance the quality of mitochondria in aging individuals and ameliorate age-related diseases.…”
Section: Mitophagymentioning
confidence: 99%
See 1 more Smart Citation
“…While Esselun et al observed that 1 μM UA had no significant effect on MMP level in control cell lines (SH-SY5Ymock) and early AD models (SH-SY5Y-APP695). Conversely, a 10-fold increased level of UA (10 μM) yielded no observable improvement other than model-specific changes and even deteriorated mitochondrial function ( 19 ). In this study, we constructed the AD model of PC12 cells in vitro , and the difference in the regulation of MMP caused by different models cannot be ignored.…”
Section: Resultsmentioning
confidence: 99%
“…Urolithin A, a main compound found in pomegranate and walnuts, demonstrated neuroprotective effect in a cellular model of AD. Urolithin A had no effect on autophagy in SH-SY5Y-APP695 cells while exerted hormetic effects through mitochondrial biogenesis which, in turn, induced the transcription of several genes [ 76 ]. A summary of the hormesis activity of natural compounds in vitro and in vivo on AD is provided in Table 3 .…”
Section: Introductionmentioning
confidence: 99%